Elusive Refuge. - Madokoro, Laura (Harvard University Press, 2016)
During the Cold War, millions of refugees left "Red China" to escape economic and political turmoil. Elusive Refuge explores the forgotten history of these refugee movements, explaining why people left, how they moved, and the international reactions to their plight. Linking immigration reforms with the politics of the Cold War, the book focuses on white settler societies - the United States, Australia, New Zealand, Canada and South Africa - to explore the tension between a vibrant transnational network of international secular and faith organizations that raised awareness about the plight of refugees in Asia and governments that were alarmed at the prospect of the refugees' arrival.--